2019
DOI: 10.1523/jneurosci.2244-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role of the Intraparietal Sulcus in Response Inhibition Predicted by Parcellation-Based Network

Abstract: The posterior parietal cortex (PPC) features close anatomical and functional relationships with the prefrontal cortex. However, the necessity of the PPC in executive functions has been questioned. The present study used the stop-signal task to examine response inhibition, an executive function that inhibits prepotent response tendency. The brain activity and resting-state functional connectivity were measured to analyze a parcellation-based network that was aimed at identifying a candidate PPC region essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 98 publications
4
58
0
Order By: Relevance
“…Together these results suggest that targeting parietal cortex may impact frontal circuits, and vice versa. Consistent with this hypothesis, stimulation to the IPS, which shows strong prefrontal connections, lead to impairments on a stop signal task compared to stimulation of the tempoparietal junction, an area not connected to the prefrontal cortex 74 . Also consistent with this network hypothesis of TMS effects, recent work has shown that prefrontal stimulation alters parietal activity 75 , and that the therapeutic effects of prefrontal stimulation may be mediated in part through these changes in parietal activity 76 .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Together these results suggest that targeting parietal cortex may impact frontal circuits, and vice versa. Consistent with this hypothesis, stimulation to the IPS, which shows strong prefrontal connections, lead to impairments on a stop signal task compared to stimulation of the tempoparietal junction, an area not connected to the prefrontal cortex 74 . Also consistent with this network hypothesis of TMS effects, recent work has shown that prefrontal stimulation alters parietal activity 75 , and that the therapeutic effects of prefrontal stimulation may be mediated in part through these changes in parietal activity 76 .…”
Section: Discussionmentioning
confidence: 66%
“…Importantly, frontoparietal interactions may be important for treatment response. Connectivity based parcellation shows that the IPS is strongly connected to prefrontal regions important for attentional processes 74 . Indeed, our previous results suggest that this region may be a cortical connectivity hub 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Frontal Eye Field decrease activity in less than 10 ms before SSRT (Hanes et al, 1998), dopaminergic neurons in rodent substantia nigra and striatum increase activity only 12 ms before SSRT (Ogasawara et al, 2018), TMS at ~25 ms before SSRT over human Intraparietal Sulcus prolongs SSRT (Osada et al, 2019), and P300 human EEG activity ~300 ms after the Stop signal relates to the stopping latency (Wessel and Aron, 2015). Whereas the rather late timing of some of these results might be related to processes such as monitoring and feedback (Huster et al, 2019) as has been ascribed to brain signatures that modulate after SSRT (Logan et al, 2015;Schall and Boucher, 2007), our earlier latencies for prefrontal bursts, TMS-MEP and muscle…”
Section: Discussionmentioning
confidence: 98%
“…This model specifies the chronometrics of stopping in more detail than extant human models, and, more generally, raises questions about the timing reported in some other studies. For example, other research has shown that movement neurons in monkey Frontal Eye Field decrease activity <10 ms before SSRT 42 , dopaminergic neurons in rodent substantia nigra and striatum increase activity 12 ms prior to SSRT 43 , TMS at ∟25 ms before SSRT over human Intraparietal Sulcus prolongs SSRT 44 , and that P300 human EEG activity ∟300 ms after the Stop signal relates to stopping speed 45 . Our observations of shorter latencies for prefrontal bursts, TMS-MEP and muscle CancelTime, raise questions about what is reflected in these late neural activities.…”
Section: Discussionmentioning
confidence: 99%